Efficient In Vivo Selection of a Novel Tumor-Associated Peptide from a Phage Display Library - Veleva, Anka N. (MDPI, 2011)
We developed a screening procedure to identify ligands from a phage display random peptide library that are selective for circulating bone marrow derived cells homing to angiogenic tumors. Panning the library on blood outgrowth endothelial cell suspension in vitro followed by in vivo selection based on homing of bone marrow-bound phage to angiogenic tumors, yielded the peptide QFPPKLTNNSML. Upon intravenous injection phage displaying this peptide homed to Lewis lung carcinoma (LLC) tumors in vivo whereas control phage did not localize to tumor tissue. Phage carrying the QFPPKLTNNSML peptide labeled with (64)Cu radionuclide when administered intravenously into a tumor bearing mouse was detected noninvasively with positron emission tomography (PET) around the tumor. These proof-of-principle experiments demonstrate the ability of the QFPPKLTNNSML peptide to deliver payload (radiolabeled phage conjugates) in vivo to sites of ongoing angiogenesis and point to its potential clinical utility in a variety of physiologic and pathologic processes where neovascular growth is a critical component.